2017
DOI: 10.3171/2016.2.jns152231
|View full text |Cite
|
Sign up to set email alerts
|

Effect of low-frequency deep brain stimulation on sensory thresholds in Parkinson's disease

Abstract: OBJECTIVE Chronic pain is a major distressing symptom of Parkinson's disease (PD) that is often undertreated. Subthalamic nucleus (STN) deep brain stimulation (DBS) delivers high-frequency stimulation (HFS) to patients with PD and has been effective in pain relief in a subset of these patients. However, up to 74% of patients develop new pain concerns while receiving STN DBS. Here the authors explore whether altering the frequency of STN DBS changes pain perception as measured through quantitative sensory testi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 59 publications
1
23
0
4
Order By: Relevance
“…We postulate that the ideal conditions for therapeutic effect in PRP occur when there is synchronicity in the β oscillatory representation of both painful and nonpainful sensations. This may underly the differential efficacy observed between LFS and HFS in modulating sensory and pain thresholds [11].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We postulate that the ideal conditions for therapeutic effect in PRP occur when there is synchronicity in the β oscillatory representation of both painful and nonpainful sensations. This may underly the differential efficacy observed between LFS and HFS in modulating sensory and pain thresholds [11].…”
Section: Discussionmentioning
confidence: 99%
“…Reports on thalamic DBS for the treatment of neuropathic pain suggest that low-frequency stimulation (LFS) is beneficial for pain relief, while high-frequency stimulation (HFS) is less efficacious or may even exacerbate pain [10]. Studies have also demonstrated that LFS can result in a lowered heat detection threshold and an increased tolerance to mechanical pain in non-neuropathic PD patients [11]. However, the nature of the physiology underlying this phenomenon remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Bis dato ist unklar, ob der analgetische Effekt der STN-THS durch einen stimulationsbedingten schmerzmodulierenden Effekt oder allein durch die Verbesserung der Motorik bedingt ist. Zu berücksichtigen ist ferner, dass auch bis 74 % der Patienten unter STN-THS über neue und/oder an anderen Körperstellen auftretende Schmerzen berichten [59,60]. Ob diese krankheitsbedingt und stimulationsunabhängig oder durch die Stimulation mitbedingt sind, ist unklar.…”
Section: Datenlage Zur Tiefen Hirnstimulation Bei Schmerzen Beim Ipsunclassified
“…Die STN-THS kann offenbar Schwellenwerte für die Erkennung thermischer [61] und/oder mechanischer Reize [57,60] verändern, vermutlich durch Beeinflussung der somatosensorischen Schleife. Die überwiegende Anzahl der Studien fand jedoch keine Hinweise auf eine Veränderung der thermischen oder mechanischen Schmerzschwellen [57,61], so dass eine Modulierung des zentralen Schmerzes durch die STN-THS nicht belegt ist.…”
Section: Datenlage Zur Tiefen Hirnstimulation Bei Schmerzen Beim Ipsunclassified
See 1 more Smart Citation